Validación de un cine foro como estrategia de prevención del consumo de alcohol y drogas en estudiantes de la Universidad Técnica Particular de Loja - Celi Jaramillo, Mariana Elizabeth (2016)
The present research refers to the "Validation of a forum theater as a strategy for prevention of alcohol and drugs use among students of the Technical University of Loja" is characterized by a design of mixed type, which uses quantitative methodology through descriptive analysis and qualitative methodology for content analysis. Its main objective is to design, implement and validate a forum theater as a strategy for prevention of alcohol and drugs in students from the Technical University of Loja, with an initial population of 50 students of the subjects of Spiritual Development. Among the results we have the criteria used for the selection of the film that were correct and well developed; a forum with the invited guest expert can develop attitudes and skills. Also it was obtained that the film forum works as a strategy for prevention of alcohol and drugs among university students and finally a guide was developed for the application of a film forum that can be used in other institutions.